2022
DOI: 10.1007/s11042-022-12332-1
|View full text |Cite
|
Sign up to set email alerts
|

Mammogram breast cancer CAD systems for mass detection and classification: a review

Abstract: Although there is an improvement in breast cancer detection and classification (CAD) tools, there are still some challenges and limitations that need more investigation. The significant development in machine learning and image processing techniques in the last ten years affected hugely the development of breast cancer CAD systems especially with the existence of deep learning models. This survey presents in a structured way, the current deep learning-based CAD system to detect and classify masses in mammograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…Hassan, et al, 16 provided a dataset-based quantitative comparison of the most recent techniques and the most commonly-used evaluation metrics for the breast cancer CAD systems. The survey also highlighted challenges and limitations of the current breast cancer detection and classification techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Hassan, et al, 16 provided a dataset-based quantitative comparison of the most recent techniques and the most commonly-used evaluation metrics for the breast cancer CAD systems. The survey also highlighted challenges and limitations of the current breast cancer detection and classification techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, WHO reported that the first or second major reason for death earlier than the age of 70 is cancer, in 112 of 183 nations. It is ranked third or fourth in the other 23 countries [1]. It causes an irregular growth of cells and is frequently named depending on the part of the body in which it occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The widely used medical breast images are Mammography [5], Positron Emission Tomography (PET) [6], Magnetic Resonance Imaging (MRI) [7], Computed Tomography (CT) [8] and Ultrasound [9]. Mammography is one of the most widely used screening methods for breast cancer [10,11] due to its low cost, better sensitivity and specificity for breast lesions, and excellent ability to detect lesions of the breast in the early stage of breast cancer [12]. A mammography breast sample contains two images with two views, that is, Craniocaudal (CC) and Mediolateral Oblique (MLO) mammographic views.…”
Section: Introductionmentioning
confidence: 99%